Integration of reservoir simulation with 3D reflection seismic time-lapse data at Ketzin - Huang, F.; Juhlin, Christopher; Kempka, T.; Norden, B. (EAGE Publishing BV, 2014)
In this study we integrate reservoir simulation with 3D reflection seismic time-lapse data from the Ketzin CO2 storage pilot site using density and velocity models, a porosity model and a fluid flow simulation model. To simulate the seismic response corresponding to the real data, detailed density and velocity models are properly generated from the stratigraphic model and available borehole logging data. The reservoir simulation model providing the spatial CO2 saturation in the reservoir based on numerical simulations history-matched to the site monitoring data is used to calculate the bulk densities and compressional wave velocities of the rock after CO2 injection using a fluid substitution method. 3D synthetic seismic data are generated by convolving the density and velocity models with two different sources to study the change in seismic response after CO2 injection and to investigate the impact of the different source types on CO2 monitoring. Our results provide estimates of the time-lapse anomalies caused by CO2 injection and demonstrate that the choice of source type is a critical factor for time-lapse seismic monitoring to assess the distribution of injected CO2. The same source type should be used in the baseline and repeat surveys for site operation.